2021
DOI: 10.3389/fmicb.2021.647452
|View full text |Cite
|
Sign up to set email alerts
|

FRET-Based Detection and Quantification of HIV-1 Virion Maturation

Abstract: HIV-1 infectivity is achieved through virion maturation. Virus particles undergo structural changes via cleavage of the Gag polyprotein mediated by the viral protease, causing the transition from an uninfectious to an infectious status. The majority of proviruses in people living with HIV-1 treated with combination antiretroviral therapy are defective with large internal deletions. Defective proviral DNA frequently preserves intact sequences capable of expressing viral structural proteins to form virus-like pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 76 publications
2
18
0
Order By: Relevance
“…The proportion of the total Gaussian distribution or kernel density estimation area overlapping with the HIV-1 Gag-iFRETDPro area was used to determine the proportion of immature virions. Image data analysis and subsequent calculations of mature and immature virion proportions were performed using an updated in-house MATLAB program [13].…”
Section: Fret-based Virion Visualizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of the total Gaussian distribution or kernel density estimation area overlapping with the HIV-1 Gag-iFRETDPro area was used to determine the proportion of immature virions. Image data analysis and subsequent calculations of mature and immature virion proportions were performed using an updated in-house MATLAB program [13].…”
Section: Fret-based Virion Visualizationmentioning
confidence: 99%
“…Our previous research developed a unique tool for detecting virus maturation utilizing a fluorescence resonance energy transfer (FRET)-based technique [13]. This approach enables the semi-automatic evaluation of virion maturation through fluorescent microscopy, effectively minimizing human bias.…”
Section: Introductionmentioning
confidence: 99%
“…VLPs have previously been employed for immunization purposes and demonstrated that immature morphology enhanced immunogenicity of VLPs and strongly induced IFN-γ secretion and antibody production ( Álvarez-Fernández et al, 2012 ; Gonelli et al, 2019 ). Approximately 20% of the virions harboring intact protease still remain immature morphology after budding ( Sarca et al, 2021 ), which implies that VLPs generated from defective proviruses might contribute to chronic inflammation in PLWH. In addition, proviruses with defective major splice donors or hypermutations induced by APOBEC3 cytidine deaminase enzymes ( Izumi et al, 2008 ; Fukuda et al, 2019 ) can produce antigens against CTL and constitutively induce their activation ( Shankar et al, 2000 ; Monajemi et al, 2014 ; Figure 4 ).…”
Section: Human Immunodeficiency Virus Persistencementioning
confidence: 99%
“…For deeper insight into cell-virion interaction more advanced fluorescence imaging methods, such as FRET, fluorescence recovery after photobleaching (FRAP) and fluorescence lifetime imaging (FLIM) are being used to visualize the virus-cell protein interactions, detection and quantification of the virus within the cell, surface receptor- binding, and so on [142,143]. For example, Gordon et al investigated SARS and MERS viral-human protein interaction using 3-Å cryoelectron microscopy, immunofluorescence, functional genetic screening and proteomics combined with cell biology [144].…”
Section: Immune Response Toward Virusmentioning
confidence: 99%